A method for preparing two-dimensional MOFs nanosheets based on self-sacrificial template method

By using amorphous metal complex nanosheets as templates based on the self-sacrificial template method, two-dimensional MOFs nanosheets with high catalytic activity were successfully prepared, which solved the poor universality of the preparation method in the prior art and blockage of active sites, and achieved excellent methanol oxidation performance and stability.

CN119176950BActive Publication Date: 2025-04-11CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411687816.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

It is difficult to effectively prepare two-dimensional MOFs nanosheets with high catalytic activity in the prior art, and the preparation method has disadvantages such as poor universality, uncontrollable nanosheet thickness, and blocking active sites.

Method used

Amorphous metal complex nanosheets were synthesized by the surfactant-free method using a method based on the self-sacrifice template, and these nanosheets were used as self-sacrifice templates to induced the synthesis of two-dimensional MOFs nanosheets through solvothermal reaction.

Benefits of technology

It realizes the efficient preparation of two-dimensional MOFs nanosheets, has excellent methanol oxidation performance and stability, and provides a novel design idea of ​​two-dimensional MOFs electrocatalysts, with potential commercial value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176950B_ABST
    Figure CN119176950B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing two-dimensional MOFs nanosheets based on a self-sacrificial template method, which belongs to the field of organic framework catalyst preparation. The present invention uses a surfactant-free method to first synthesize amorphous metal complex nanosheets M / CNS (M=Co, Ni, Cu, CoNi, CoCu, NiCu), and then uses the prepared M / CNS as a self-sacrificial template to induce the synthesis of two-dimensional MOFs nanosheets M / MNS (M=Co, Ni, Cu, CoNi, CoCu, NiCu). Experimental results show that the two-dimensional MOFs nanosheets M / MNS obtained by reacting at 150° C. for 6 hours in a solvent thermal reactor with DMA as a solvent, M / CNS (M=NiCu) as a self-sacrificial template, and terephthalic acid as a ligand have excellent methanol electro-oxidation catalytic performance and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic framework catalyst preparation, and specifically is a method for preparing two-dimensional MOFs nanosheets based on a self-sacrificial template method. Background Art

[0002] A large number of studies have shown that metal / metal oxide / porous carbon nanocomposites prepared using MOFs have high catalytic activity and are therefore considered to be ideal catalysts for methanol oxidation reactions. However, MOFs catalysts prepared from different metals have different performances, and MOFs catalysts prepared under different preparation conditions have different activities.

[0003] Recently, two-dimensional nanomaterials such as graphene, graphene-phase carbon nitride, transition metal oxides, transition metal halides and double hydroxides have attracted people's attention because of their extraordinary physical and chemical properties, which has also inspired people to synthesize two-dimensional MOFs nanosheets. However, the synthesis of two-dimensional MOFs nanosheets is still a huge challenge because it is difficult to limit the growth of MOFs crystals to a thickness of a few nanometers without affecting lateral growth. At present, several methods for preparing two-dimensional MOFs nanosheets have been developed, such as ultrasound-assisted exfoliation, two-phase interface method, organic surfactant method, etc. However, the above methods have the disadvantages of poor universality, uncontrollable nanosheet thickness, and blocked active sites. Therefore, a new method for preparing two-dimensional MOFs nanosheets continues to be developed. Summary of the invention

[0004] In order to improve the catalytic activity of two-dimensional MOFs nanosheets, the present invention provides a method for preparing two-dimensional MOFs nanosheets based on a self-sacrificial template method.

[0005] The present invention utilizes a surfactant-free method to first synthesize amorphous metal complex nanosheets (M / CNS), such as copper ethylenediaminetetraacetate, nickel ethylenediaminetetraacetate, nickel oxyethylenediaminetetraacetate and the like, and then uses them as self-sacrificial templates to induce the synthesis of two-dimensional MOFs nanosheets (M / MNS).

[0006] Technical solution: A method for preparing two-dimensional MOFs nanosheets based on a self-sacrificial template method, characterized in that it comprises the following steps:

[0007] Step 1: Preparation of monometallic or bimetallic amorphous metal complex nanosheets M / CNS:

[0008] Step 1.1, dissolving metal nitrate in deionized water to obtain solution A, wherein the metal is one or two of Ni, Cu, and Co;

[0009] Step 1.2, dissolving ethylenediaminetetraacetic acid sodium salt in deionized water to obtain solution B;

[0010] Step 1.3, slowly adding solution B dropwise to solution A, centrifuging, washing, and drying the precipitate to obtain M / CNS; in M / CNS, M is any one of Co, Ni, Cu, CoNi, CoCu, and NiCu;

[0011] Step 2: Using the M / CNS prepared in step 1 as a self-sacrificial template to induce the synthesis of two-dimensional MOFs nanosheets M / MNS:

[0012] Step 2.1: Disperse M / CNS by ultrasonic N,N - Suspension C is obtained from dimethylacetamide solution;

[0013] Step 2.2, dissolve terephthalic acid in N,N -solution D obtained from dimethylacetamide;

[0014] Step 2.3, slowly add solution C dropwise to solution D, disperse evenly by ultrasonication, and transfer the mixture to a stainless steel reactor for solvothermal reaction; after the reaction, centrifuge, wash, and dry the precipitate to obtain M / MNS.

[0015] Furthermore, in the step 1.1, when the metals are two of Ni, Cu and Co, the molar ratio of the two metals is 1:1.

[0016] Furthermore, in step 1.1, the amount of metal nitrate added is 0.5-0.8 g, and the volume of deionized water is 50-100 mL; in step 1.2, the amount of ethylenediaminetetraacetic acid sodium salt added is 0.8-1.0 g, and the volume of deionized water is 50-100 mL.

[0017] Preferably, in the step 1.1, the amount of metal nitrate added is 0.5 g, the metal is preferably Ni and Cu, and the molar ratio of Ni to Cu is 1:1, and the volume of deionized water is 50 mL; in the step 1.2, the amount of ethylenediaminetetraacetic acid sodium salt added is 1.0 g, and the volume of deionized water is 100 mL.

[0018] Furthermore, the mass of M / CNS in step 2.1 is 25 mg. N,N -The volume of dimethylacetamide is 3 mL; the mass ratio of terephthalic acid in step 2.2 to M / CNS in step 2.1 is (1.0-2.5): 1, N,N -The volume of dimethylacetamide is 9-12 mL.

[0019] Preferably, in step 2.2, the mass ratio of terephthalic acid to M / CNS is 1:1; N,N -The volume of dimethylacetamide is 12 mL.

[0020] Furthermore, the solvent thermal reaction conditions in step 2.3 are 150° C., heating for 3-12 hours, preferably heating for 6 hours.

[0021] Beneficial effects:

[0022] (1) The present invention synthesizes amorphous metal complex nanosheets by a room temperature wet chemical method. The method is simple to operate, economical, environmentally friendly, and has good universality. The obtained amorphous metal complex nanosheets have controllable morphology and moderate thickness.

[0023] (2) The present invention uses synthesized amorphous metal complex nanosheets as self-sacrificial templates and can prepare novel two-dimensional MOFs nanosheets under simple solvothermal conditions. This method provides a reference idea for the design of new two-dimensional MOFs electrocatalysts;

[0024] (3) The two-dimensional MOFs nanosheets of the present invention are simple to prepare and inexpensive, exhibit excellent methanol oxidation performance and stability, and have potential commercial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM images of NiCu / CNS and NiCu / MNS-6-1.0 prepared in the examples; wherein, (a) and (b) are SEM images of NiCu / CNS, and (c) and (d) are SEM images of NiCu / MNS-6-1.0.

[0026] Figure 2 Graph showing the N2 adsorption-desorption isotherms of NiCu / CNS and NiCu / MNS-6-1.0 prepared in the examples.

[0027] Figure 3 The XRD patterns of NiCu / CNS and NiCu / MNS-6-1.0 prepared in the examples are shown in FIG.

[0028] Figure 4 The infrared images of NiCu / CNS, NiCu / MNS-6-1.0 and NiCu / MNS-12-1.0 prepared in the examples are shown.

[0029] Figure 5 XPS spectra of NiCu / CNS and NiCu / MNS-6-1.0 prepared in the examples: a is the full scan spectrum; b is the O 1s spectrum; c is the Cu 2p spectrum; d is the Ni 2p spectrum.

[0030] Figure 6CV curves of different NiCu / CNS prepared in the examples in 0.5M MeOH+1M KOH solution and 1M KOH solution, respectively; wherein, a is the CV curve of different NiCu / CNS in 0.5M MeOH+1M KOH solution; b is the CV curve of different NiCu / CNS in 1M KOH solution.

[0031] Figure 7 CV curves of NiCu / CNS prepared in the examples in 0.5M MeOH+1M KOH solution: wherein a represents NiCu / CNS with different Cu / Ni ratios; b represents NiCu / CNS with different reaction times and terephthalic acid addition amounts.

[0032] Figure 8 CV curves of NiCu / MNS-6-1.0 in 0.5M MeOH+1M KOH solution and 1M KOH solution, respectively, and chronoamperometric curves in 0.5M MeOH+1M KOH solution in the embodiment; wherein, a is the CV curves of NiCu / MNS-6-1.0 in 0.5M MeOH+1M KOH solution and 1M KOH solution, respectively, in the embodiment; b is the chronoamperometric curve of NiCu / MNS-6-1.0 in 0.5M MeOH+1M KOH solution.

[0033] Fig. 9 It is a schematic diagram of the process of the preparation method of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0035] Example 1: A method for preparing two-dimensional MOFs nanosheets based on a self-sacrificial template method

[0036] The main raw materials involved in the embodiments of the present invention are as follows:

[0037]

[0038] (I) The experimental setup of this embodiment is as follows:

[0039] Step 1: Preparation of monometallic or bimetallic amorphous metal complex nanosheets M / CNS:

[0040] Step 1.1, dissolving metal nitrate in deionized water to obtain solution A, wherein the metal is one or two of Ni, Cu, and Co; in step 1.1, when the metal is two metals, the molar ratio of the two metals is 1:1;

[0041] Specifically, an example of the configuration of a single metal or bimetallic solution A is as follows: when the metal is one type and is nickel nitrate hexahydrate, 0.5 g of Ni(NO3)2·6H2O is weighed and stirred in 50 mL of deionized water for 10 minutes, which is referred to as liquid A; when the metals are two types, nickel nitrate hexahydrate and cobalt nitrate hexahydrate, 0.25 g of Ni(NO3)2·6H2O and 0.25 g of Co(NO3)2·6H2O are weighed and stirred in 50 mL of deionized water for 10 minutes, which is referred to as liquid A. At this time, the molar ratio of Ni to Co is 1:1.

[0042] Step 1.2, weigh 1.0 g of sodium ethylenediaminetetraacetate and dissolve it in 100 mL of deionized water by ultrasonication, which is called solution B;

[0043] Step 1.3, slowly drop solution B into solution A, stir and react for 30 minutes, then centrifuge, wash and dry the precipitate to obtain M / CNS. In M / CNS, M is any one of Co, Ni, Cu, CoNi, CoCu and NiCu.

[0044] Step 2: Using the M / CNS prepared in step 1 as a self-sacrificial template to induce the synthesis of two-dimensional MOFs nanosheets M / MNS:

[0045] Step 2.1: Weigh 25 mg of M / CNS and disperse it in 3 mL N,N - Suspension C is obtained from dimethylacetamide solution;

[0046] Step 2.2: Weigh terephthalic acid and dissolve it in 12 mL N,N -dimethylacetamide to obtain solution D.

[0047] In the step 2.2, the mass ratio of terephthalic acid to M / CNS is set to 1:1 and 2.5:1, or no terephthalic acid is added, as a reference;

[0048] Step 2.3, solution C is slowly added dropwise to solution D, ultrasonically dispersed evenly, and the mixture is transferred to a stainless steel reactor for solvothermal reaction. After the reaction is completed, the precipitate is centrifuged, washed, and dried to obtain M / MNS.

[0049] In the step 2.3, the solvent thermal reaction condition is 150° C. and heating for 3-12 hours.

[0050] In this embodiment, a series of M / MNS were synthesized by the controlled variable method and named M / MNS-XY (M = Co, Ni, Cu, CoNi, CoCu or NiCu; X is the reaction time (h), and Y is the mass ratio of terephthalic acid to M / CNS) for distinction. For example, when the self-sacrificial template used is NiCu / CNS, the mass ratio of terephthalic acid to M / CNS is 1:1, and the M / MNS-XY obtained by the solvent thermal reaction for 6 hours can be expressed as NiCu / MNS-6-1.0. Its structure was characterized by means of XRD, SEM, TEM, etc., and its electrocatalytic performance of methanol oxidation was determined.

[0051] (II) Example The structural characterization results of the two-dimensional MOFs nanosheets prepared are as follows:

[0052] (1) SEM, BET and XRD tests

[0053] The morphology and structure of NiCu / CNS precursor and two-dimensional MOFs nanosheets NiCu / MNS-6-1.0 were studied by scanning electron microscopy ( Figure 1 ).like Figure 1 As shown in (a) and (b), the prepared NiCu / CNS presents a layered stacked nanosheet morphology with a length of 5–10 μm, a width of 4–6 μm, and a thickness of less than 20 nm. The surface of NiCu / CNS is relatively smooth overall, with only a few raised wrinkles in local areas. Figure 1 As shown in (c) and (d), NiCu / MNS-6-1.0 presents a cross-linked nanosheet morphology, and the size of the nanosheet is smaller, with a length of 200-300 nm, a width of 100-200 μm, and a thickness of less than 10 nm. This result shows that during the hydrothermal reaction, the unique nanosheet morphology of the NiCu / CNS template can promote the growth of MOFs along a specific direction, and the tiny gaps formed by the partially etched NiCu / CNS limit the further growth of NiCu / MNS-6-1.0, thereby obtaining a smaller cross-nanosheet.

[0054] The specific surface areas of the samples were further determined using N2 adsorption-desorption isotherms. The specific surface areas of NiCu / CNS and NiCu / MNS-6-1.0 were 327.0281 m 2 ·g −1 and 349.6985m 2 ·g −1 ( Figure 2 Compared with the large-sized nanosheets of NiCu / CNS layered stacks, NiCu / MNS-6-1.0 has a larger specific surface area.

[0055] Subsequently, the phase analysis of NiCu / CNS and NiCu / MNS-6-1.0 catalysts was carried out by X-ray diffraction. Figure 3 As shown in Figure 2, the prepared NiCu / CNS has no significant diffraction peaks, which is related to the amorphous morphology of NiCu / CNS solid. θ = 9.2°, 16.1°, 17.5° and 28.7° have significant diffraction peak intensities, which is consistent with the NiBDC crystal structure reported in the literature (CCDC NO: 638866, JCPDS NO: 035-1671). It is worth noting that the signal-to-noise ratio of the XRD spectrum of NiCu / MNS-6-1.0 is poor, which may be related to the smaller nano size of NiCu / MNS-6-1.0.

[0056] (2) Infrared analysis and X-ray photoelectron spectroscopy analysis

[0057] In order to further explore the structural information of two-dimensional MOFs nanosheets, this example uses Fourier transform infrared spectroscopy to characterize the catalyst. Figure 4 As shown by the black line, at 3424 cm -1 The broad and intense signal peaks appearing near the wavenumber are attributed to the stretching vibration of the N–H bond of the amino functional group in the ethylenediaminetetraacetic acid ligand of NiCu / CNS. Different from the NiCu / CNS precursor, NiCu / MNS-6-1.0 and NiCu / MNS-12-1.0 have the peaks at 1500, 1400, 1050, 740 and 560 cm -1 New absorption peaks appeared near the same wave number. Among them, 1500 cm -1 The absorption peaks near the wavenumbers 1400, 1050, 740 and 560 cm-1 are related to the stretching vibration of the C=O double bond of the carboxyl functional group of the terephthalic acid ligand. -1 The absorption peaks near the same wave number belong to the benzene ring fingerprint peaks of the terephthalic acid ligands. These results prove that the ligands in the NiCu / CNS template are gradually replaced by the newly added terephthalic acid during the solvothermal reaction. Finally, the elemental composition and electronic state of the NiCu / CNS precursor and the two-dimensional MOFs nanosheet NiCu / MNS-6-1.0 were characterized by X-ray photoelectron spectroscopy. Figure 5As shown in the full XPS scan spectrum of NiCu / CNS, characteristic peaks of Cu (932.9 eV), Ni (855.4 eV), O (529.4 eV), and C (285.0 eV) can be observed. After terephthalic acid and sodium ethylenediaminetetraacetic acid undergo ligand exchange, the characteristic peaks of O and C at 529.4 eV and 285.0 eV of NiCu / MNS-6-1.0 increase significantly, indicating that NiCu / CNS reacts successfully with terephthalic acid. Compared with NiCu / CNS, the Cu 2p and Ni The binding energy of 2p is reduced, which is speculated to be due to the introduction of terephthalic acid changing the environment around the activation center. Figure 5 c and d. After the introduction of terephthalic acid, the binding energies of O, Cu, Ni and other elements in NiCu / MNS-6-1.0 increased by 0.5, 2.01 and 0.05 eV respectively compared with NiCu / CNS, indicating that the addition of terephthalic acid changed the structure of NiCu / CNS and the electronic configuration of the metal also changed significantly.

[0058] 3. Study on the performance of electrocatalytic methanol oxidation:

[0059] The electrochemical test was carried out in a three-electrode system and controlled by a CHI760E electrochemical workstation. The working electrode was a glassy carbon electrode (0.1962 cm 2 ), inner diameter 5 mm, reference electrode is Hg / HgO electrode, auxiliary electrode is platinum wire electrode. The catalyst ink consists of two parts: (1) dispersed 2.5 mg catalyst and 2.5 mg carbon black; (2) 1 ml of solution required for dispersion contains 950 μL isopropanol and 50 μL Nafion binder. A total of 10 μL of catalyst dispersion is applied on the polished GC electrode in batches and dried at room temperature before use. The loading capacity of the glassy carbon electrode is 0.127 mg / cm 2 , so that the load capacity of all samples remains consistent and easy to compare.

[0060] (1) Study the effect of M / MNS electrocatalysts with different metal compositions on the methanol oxidation performance. Figure 6 As shown in Figure 2, the electrocatalytic performance of M / MNS with different metal compositions was tested by cyclic voltammetry (CV). The CV test was first carried out in a mixed solution containing 1.0 M MKOH and 0.5 M methanol. Both single-metal or bimetallic M / MNS showed certain catalytic methanol oxidation performance, as shown in Figure 2. Figure 6In a, the anodic response current of the bimetallic NiCu / MNS electrocatalyst is significantly higher than that of the monometallic Ni / MNS, Cu / MNS, Co / MNS and the bimetallic CoCu / MNS, NiCo / MNS electrocatalysts, indicating that NiCu / MNS nanosheets have excellent electrocatalytic activity for methanol oxidation. In order to exclude the interference of the competitive water oxidation reaction, the methanol oxidation performance catalyzed by the above M / MNS was compared with that of water oxidation, as shown in Figure 2. Figure 6 As shown in (b), NiCu / MNS requires a lower starting potential than water oxidation to reach 10 mA / cm 2 The current density of NiCu / MNS shows that NiCu / MNS has a good electrochemical response to methanol oxidation. NiCu / MNS has a unique cross-nanosheet morphology, which can provide a large number of active sites and promote the penetration of reactants. In addition, the electronegativity difference between Ni and Cu metals is conducive to regulating the local electronic structure and improving the electrocatalytic activity.

[0061] (2) Study the effect of Ni / Cu ratio of NiCu / MNS-based electrocatalyst on methanol oxidation performance. Figure 7 As shown in a, when X is 6 and Y is 1:1, the CV curve of Cu:Ni = 1:1 is the steepest (a smaller applied voltage produces the largest electrolysis current), indicating that it has the best methanol oxidation performance under the same reaction conditions. The study also found that the anodic oxidation curves of Cu:Ni = 1:4 and Cu:Ni = 2:3 are higher than those of Cu:Ni = 3:2 and Cu:Ni = 4:1, indicating that Ni plays a decisive role in the active components of NiCu-MNS. However, in Cu:Ni = 1:4, Cu:Ni = 2:3 and Cu:Ni = 1:1, as the Ni content decreases, the performance of NiCu-MNS gradually increases, indicating that although Ni plays a decisive role in NiCu-MNS, too much Ni reduces the performance.

[0062] (3) Study the effects of different reaction times and terephthalic acid addition amounts on methanol oxidation performance. Figure 7 As shown in middle b, NiCu / MNS-6-1.0 obtained by solvothermal reaction for 6 hours with NiCu / CNS as self-sacrificial template and the mass ratio of terephthalic acid to M / CNS being 1:1 has the best methanol oxidation performance.

[0063] (4) If Figure 8 As shown, after deducting the background interference of competitive water oxidation reaction, the highest current density of NiCu / MNS-6-1.0 is ΔJ =167 mA / cm 2 In addition, NiCu / MNS-6-1.0 at 100 mA / cm 2It worked continuously for 10,000 seconds in the constant current mode without obvious deactivation, showing good stability.

[0064] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention.

Claims

1. A method for preparing two-dimensional MOFs nanosheets based on a self-sacrificial template method, characterized in that: The steps include: Step 1: Preparation of bimetallic amorphous metal complex nanosheets M / CNS: Step 1.1, dissolving metal nitrate in deionized water to obtain solution A, wherein the metal is two of Ni, Cu and Co, and the molar ratio of the two metals is 1:1; Step 1.2, dissolving ethylenediaminetetraacetic acid sodium salt in deionized water to obtain solution B; Step 1.3, slowly adding solution B dropwise to solution A, centrifuging, washing, and drying the precipitate to obtain M / CNS; in M / CNS, M is any one of CoNi, CoCu, and NiCu; Step 2: Using the M / CNS prepared in step 1 as a self-sacrificial template to induce the synthesis of two-dimensional MOFs nanosheets M / MNS: Step 2.1: Disperse M / CNS by ultrasonic N,N - Suspension C is obtained from dimethylacetamide solution; Step 2.2, dissolve terephthalic acid in N,N -solution D obtained from dimethylacetamide; the mass ratio of terephthalic acid in step 2.2 to M / CNS in step 2.1 is (1.0-2.5): 1; Step 2.3, slowly drop solution C into solution D, disperse evenly by ultrasonication, and transfer the mixture to a stainless steel reactor for solvothermal reaction; after the reaction, centrifuge, wash, and dry the precipitate to obtain M / MNS; the solvothermal reaction conditions in step 2.3 are 150°C and heating for 3-12 hours.

2. The preparation method according to claim 1, characterized in that: In the step 1.1, the amount of metal nitrate added is 0.5-0.8 g, and the volume of deionized water is 50-100 mL; in the step 1.2, the amount of ethylenediaminetetraacetic acid sodium salt added is 0.8-1.0 g, and the volume of deionized water is 50-100 mL.

3. The preparation method according to claim 2, characterized in that: In the step 1.1, the amount of metal nitrate added is 0.5 g, the metals are Ni and Cu, and the molar ratio of Ni to Cu is 1:1, and the volume of deionized water is 50 mL; in the step 1.2, the amount of ethylenediaminetetraacetic acid sodium salt added is 1.0 g, and the volume of deionized water is 100 mL.

4. The preparation method according to claim 1, characterized in that: The mass of M / CNS in step 2.1 is 25 mg. N,N -The volume of dimethylacetamide is 3 mL; In step 2.2, N,N -The volume of dimethylacetamide is 9-12 mL.

5. The preparation method according to claim 4, characterized in that: The mass ratio of terephthalic acid in step 2.2 to M / CNS in step 2.1 is 1:1; N,N -The volume of dimethylacetamide is 12 mL.

6. The preparation method according to claim 5, characterized in that: The heating time in step 2.3 is 6 hours.

Citation Information

Patent Citations

  • Two-dimensional CuBDC nanosheet and preparation method thereof

    CN117757089A